Pleroma goyazense (Melastomataceae), a new species from Goiás state, Brazil, and a new synonym in Pleroma - Machado, Ana Isa Marquez Rocha; Romero, Rosana; Guimarães, Paulo José Fernandes (Phytotaxa, 2023)
We describe here the new species Pleroma goyazense, including illustrations, geographic distribution, habitat data, and preliminary conservation status according to the International Union for Conservation of Nature (IUCN) Red list criteria. We also propose to synonymize Pleroma nodosum under Pleroma robustum, a decision corroborated by the study of Pleroma species with similarities to P. goyazense. Pleroma goyazense is endemic to the state of Goiás, Brazil, occurring in cerrado rupestre (rupestrine savanna) on rocky outcrops or crevices, environments that are also shared by similar species P. crassirame and P. robustum. Pleroma goyazense differs from P. crassirame in having sparsely leaves arranged on the upper branches and pedoconnective stamens with a dorsal appendage. It also differs from P. robustum in having lanceolate, non-involucral bracteoles, and sepals acuminate at the apex.